Diagnostic Validity of Ultrasonography in Evaluation of Biliary Obstruction and its Comparison with Magnetic Resonance Cholangiopancreatography (Bangladesh Journal of Radiology and Imaging, 2026)
Objective: To assess the diagnostic validity of ultrasonography in evaluation of biliary obstruction and its comparison with magneticresonance cholangiopancreatography. Methods: This cross sectional study was carried out in the Department of Radiology and Imaging, Combined Military Hospital, Dhaka, during the period of October 2021 to March 2022 (6 months). The sampling technique was purposive and sample size was 60. The patient attending the (outpatient department) OPD and admitted in indoor in Combined Military Hospital, Dhaka, who referredto the Radiology and Imaging department for ultrasonography and magnetic resonance cholangiopancreatography were included in the study. After selection of the patient, informed written consent were obtained from the patients or their legal guardians upon describing them the purpose, method, benefit and hazard of the study. Ethical measures were taken in throughout the study. Data collection was done by the researcher and a preformed questionnaire was used during data collection. Following completion of datacollection, it was analyzed by SPSS 23.0. Results: Total 60 patients were studied with an age range from 9 years to 75 years. Mean age of the included patients was 47.8 years with a standard deviation of 12.4 years. Study showed a female dominance with a male-female ratio of about 1:1.2. Regardingthe cause of obstruction 40.0% patients had choledocholithiasis (CBD stone), followed by 20% infiltrating GB mass, 16.66% cholangiocarcinoma, 10% periampullary carcinoma, 11.66% carcinoma head of the pancreas, 1.6% had choledochal cyst.The validity test of ultrasonographic evaluation for choledocholithiasis in obstructive jaundice had sensitivity 87.5%, specificity 100%, accuracy 95%, positive predictive values 100% and negative predictive values 92.3%.The validity test of ultrasonographic evaluation for cholangiocarcinoma in obstructive jaundice had sensitivity 80%, specificity 100%, accuracy 96.6%, positive predictive values 100% and negative predictive values 96.1%. The validity test of ultrasonographic evaluation for periampullary carcinoma in obstructive jaundice had sensitivity 83.3%, specificity 98.1%, accuracy 96.6%, positive predictive values 83.3% and negative predictive values 98.1%. The validity test of ultrasonographic evaluation for infiltrating GB mass in obstructive jaundice had sensitivity 100.0%, specificity 97.9%,accuracy 98.3%, positive predictive values 92.3% and negative predictive values 100.0%. The validity test of ultrasonographic evaluation for pancreatic head carcinoma in obstructive jaundice had sensitivity 85.7%, specificity 100%, accuracy 98.3%, positive predictive values 100% and negative predictive values 98.1%. The validity test of ultrasonographic evaluation for choledochal cyst in obstructive jaundice had sensitivity 100.0%, specificity 100.0%, accuracy 100.0%, positive predictive values 100.0% and negative predictive values 100.0%. Conclusion: Ultrasonography is an effective & good modality in the evaluation of biliary obstruction.